Six Characters in Search of a Security Problem: Pirandellian Masks for Security Ceremonies - Martimiano, Taciane; Martina, Jean Everson (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2022.225346, 2022)
For the Italian play-writer and 1934 Nobel-Prize winner Luigi Pirandello, a fictional mask is either self-imposed or, in most cases, forced on by society, being what makes life possible. Drawing from that, we believe that due to the non-deterministic nature of the human being, the only way to specify and verify human-tailored security protocols (known as security ceremonies) is by the specification of masks that users wear in order to interact with ceremonies. In the current paper, we review further this literary inspiration and propose six possible masks: the Attentive, the Naive, the Careless, the Fearful, the Busy, and the Elder. We then discuss an example of how we can reason about security involving human beings, and present what still needs to be done.